Numerical Simulation of a Lee Wave Case over Three-Dimensional Mountainous Terrain under Strong Wind Condition - Lei Li (Advances in Meteorology, 2013)
This study of a lee wave event over three-dimensional (3D) mountainous terrain in Lantau Island, Hong Kong, using a simulation combining mesoscale model and computational fluid dynamics (CFD) model has shown that (1) 3D steep mountainous terrain can trigger small scale lee waves under strong wind condition, and the horizontal extent of the wave structure is in a dimension of few kilometers and corresponds to the dimension of the horizontal cross-section of the mountain; (2) the life cycle of the lee wave is short, and the wave structures will continuously form roughly in the same location, then gradually move downstream, and dissipate over time; (3) the lee wave triggered by the mountainous terrain in this case can be categorized into “nonsymmetric vortex shedding” or “turbulent wake,” as defined before based on water tank experiments; (4) the magnitude of the wave is related to strength of wind shear. This study also shows that a simulation combining mesoscale model and CFD can capture complex wave structure in the boundary layer over realistic 3D steep terrain, and have a potential value for operational jobs on air traffic warning, wind energy utilization, and atmospheric environmental assessment.